Motives for Playing Free-Fire Online Video Game Among 13 to 17 Years Old School Students in Chennai - Sagayaraj P, Maria (Journal of Advanced Research in Journalism & Mass Communication, 2023)
The research article would be analyzing the movies for playing free-fire online video game among 13 to 17 years of school-going students in Chennai. The rise of online gaming has aided in gaming addiction which leads to various physical and psychological problems. The study chose 100 samples to assess the different factors such as social needs, personal needs, affective needs, and tension-free needs. Based on the analysis done, male players were more compared to female players. Players of the free-fire online video game, feel happy when they are ranked high among their friends. Though many factors impact the players, affective needs play a significant role in influencing players towards laying online free-fire video game. How to cite this article: Sagayaraj MP. Motives for Playing Free-Fire Online Video Game Among 13 to 17 Years Old School Students in Chennai. J Adv Res Jrnl Mass Comm 2023; 10(2): 26-31. DOI: https://doi.org/10.24321/2395.3810.2023012